2022
DOI: 10.1101/2022.02.28.482330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hominoid-specific sulcal variability is related to face perception ability

Abstract: Human perception requires complex cortical networks that function at neuroanatomical scales of microns and temporal scales of milliseconds. Despite this complexity, what if just one morphological feature of the brain could predict perceptual ability? Here, we tested this hypothesis with pre-registered analyses of neuroanatomy and face perception in neurotypical controls (NTs) and individuals with developmental prosopagnosia (DPs). Results show that the length of the mid- fusiform sulcus (MFS), a hominoid-speci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 32 publications
(62 reference statements)
3
11
0
Order By: Relevance
“…First and second, the largest effect was that individual differences in cortical thickness across all VTC and PMC sulci were larger in individuals with ASD compared to NTs – replicating and extending previous findings (Ammons et al, 2021) to other sulci in VTC aside from the MFS, as well as to PMC sulci. Third, the MFS was shorter in individuals with ASD compared to NTs, which is consistent with recent findings showing that the MFS is also shorter in individuals with developmental prosopagnosia compared to NTs (Parker et al, 2022). Fourth, correlation analyses between tertiary sulci in both regions revealed that some, but not all, tertiary sulcal morphological features of VTC and PMC are correlated in ASD individuals.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…First and second, the largest effect was that individual differences in cortical thickness across all VTC and PMC sulci were larger in individuals with ASD compared to NTs – replicating and extending previous findings (Ammons et al, 2021) to other sulci in VTC aside from the MFS, as well as to PMC sulci. Third, the MFS was shorter in individuals with ASD compared to NTs, which is consistent with recent findings showing that the MFS is also shorter in individuals with developmental prosopagnosia compared to NTs (Parker et al, 2022). Fourth, correlation analyses between tertiary sulci in both regions revealed that some, but not all, tertiary sulcal morphological features of VTC and PMC are correlated in ASD individuals.…”
Section: Discussionsupporting
confidence: 91%
“…Given recent work identifying a shorter MFS length in individuals with developmental prosopagnosia compared to NTs (Parker et al, 2022), we tested whether the length of the MFS (in mm) differed between ASD and NT participants using a 2-way ANCOVA (controlling for age) with group (ASD, NT) and hemisphere (left, right) as factors. There was a main effect of group (F(1,195) = 6.86, p = .03, η 2 G = 0.034), with no hemisphere interaction ( p = .71), in which individuals with ASD had a shorter MFS than NTs in both hemispheres ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations